Anna Tumarkin – the first female doctor of philosophy in Europe. Unknown pages of her life - Zabolotnaya, Lilia (Balcanica Posnaniensia. Acta et studia, 2009)
The article by Liliya Zabolotnaya is devoted to the outstanding figure of Anna Pavlovna Tumarkin (1875–1951) — the first woman in Europe to receive a Doctor of Philosophy degree and to become a professor of philosophy at the University of Bern. The study is set within the broad historical and cultural context of the late 19th and early 20th centuries, a period when women gradually began to gain access to higher education and academic work, overcoming persistent social and institutional barriers. The purpose of the research is to reveal the little-known pages of Anna Tumarkin’s biography, clarify her contribution to the development of European philosophical thought, and reconstruct the history of her family, connected with Belarus, Bessarabia, and Switzerland. Particular attention is given to Tumarkin’s role in the women’s movement, her academic interests in aesthetics, psychology, and the history of philosophy, as well as the professional recognition she achieved in a predominantly male academic environment. The source base of the study includes archival materials from the National Archives of the Republic of Moldova, periodical publications from the late 19th and early 20th centuries, and memoir and scholarly works published in Switzerland, Belarus, and Moldova. Methodologically, the author employs historical-biographical and comparative-analytical approaches that combine documentary evidence with an analysis of the cultural and social context of the period. The main conclusions highlight previously unknown facts from the life and work of Anna Tumarkin and her family, emphasizing her pioneering role as one of the first women to gain recognition in European philosophical scholarship. Zabolotnaya’s study contributes to restoring historical justice and preserving the memory of a woman who became a symbol of intellectual emancipation and academic courage.